Application of the domestic modified paint and varnish materials for anticorrosive protection - Тарелин, А.А.; Сурду, Н.В.; Паршина, Т.Н. (Eastern-European Journal of Enterprise Technologies, 2010)
Experience of application of coating compositions on the basis of modified polyurethane, epoxy and epoxy-urethane joints for the device of anticorrosive protection of the equipment of chemical water machining warmly power stations is resulted.